2018
DOI: 10.1016/j.celrep.2018.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Deficiency Promotes Hepatic Steatosis via a Glucocorticoid Receptor-Dependent Mechanism in Mice

Abstract: SUMMARY Glucocorticoids (GCs) are master regulators of systemic metabolism. Intriguingly, Cushing’s syndrome, a disorder of excessive GCs, phenocopies several menopause-induced metabolic pathologies. Here, we show that the glucocorticoid receptor (GR) drives steatosis in hypogonadal female mice because hepatocyte-specific GR knockout mice are refractory to developing ovariectomy-induced steatosis. Intriguingly, transcriptional profiling revealed that ovariectomy elicits hepatic GC hypersensitivity globally. Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 57 publications
1
74
0
Order By: Relevance
“…The gender difference of the metabolic disturbance is most evident in postmenopausal women. Although the mechanism of menopause-induced metabolic dysfunction are largely unknown, estrogen depletion is thought to responsible for the underlying pathological mechanism (31). This observation requires further study to confirm.…”
Section: Discussionmentioning
confidence: 96%
“…The gender difference of the metabolic disturbance is most evident in postmenopausal women. Although the mechanism of menopause-induced metabolic dysfunction are largely unknown, estrogen depletion is thought to responsible for the underlying pathological mechanism (31). This observation requires further study to confirm.…”
Section: Discussionmentioning
confidence: 96%
“…The gender difference of the metabolic disturbance is most evident in postmenopausal women. Although the mechanisms of menopause-induced metabolic dysfunction are largely unknown, estrogen depletion is thought to responsible for the underlying pathological mechanism [31]. This observation requires further study to confirm.…”
Section: Discussionmentioning
confidence: 97%
“…Bilateral ovariectomy in mice was performed as described in ref. 35. Breeding, maintenance, and experimental manipulation of mice were approved by the animal care and use committee of the IGBMC/ICS.…”
Section: Methodsmentioning
confidence: 99%
“…In Marked Contrast with Dex, a 1-Mo Treatment with CpdX Decreases the Plasmatic Glucose Level and Liver Lipid Deposition in OVX Mice. It has been reported that an estrogen deficiency can lead to hyperglycemia and a fatty liver lipid deposition in the liver of postmenopausal women (34) as well as in the livers of 4-mo-old mice that were OVX at the age of 4 wk (35). It is also known that a long-term treatment with GCs (Dex) can aggravate these metabolic and hepatic syndromes (35).…”
Section: Unlike Dex a 3-mo Treatment With Cpdx Cpdx-d3 Or Any Of Tmentioning
confidence: 99%
See 1 more Smart Citation